Antimicrobial and Anti-inflammatory Cyclic Tetrapeptides from the Co-cultures of Two Marine-Derived Fungi - Li, Qin; Li, Shasha; Li, Shunwang; Hao, Xiaomeng; Wang, Anqi; Si, Shuyi; Xu, Yanni; Shu, Jicheng; Gan, Maoluo (Journal of natural products (Washington, D.C.), 2024)
Violaceotides B–E (1–4), four new cyclic tetrapeptides, along with seven known compounds, were identified from the sponge-associated Aspergillus insulicola IMB18-072 co-cultivated with the marine-derived Alternaria angustiovoidea IMB20-805. Their structures were elucidated by extensive analysis of spectroscopic data, including HRESIMS, 1D and 2D NMR, and MS/MS data. The absolute configurations were determined by the advanced Marfey’s method. Compounds 2, 3, and violaceotide A (5) displayed selective antimicrobial activities against the aquatic pathogenic bacteria Edwardsiella tarda and E. ictaluri. In addition, compounds 1–5 showed inhibitory activities against the LPS-induced expression of the inflammatory mediator IL-6 in RAW264.7 cells at a concentration of 10 μM.